Surgical Techniques for Kidney Cancer (Springer New York, 2018)
Surgical Techniques for Kidney Cancer provides a comprehensive review and detailed description of surgical techniques for kidney and adrenal cancer. Through a step by step approach various surgical techniques are covered including radical nephrectomy, partial nephrectomy, and thermal ablation for renal cortical tumors. Each step by step approach is followed by the latest data on outcomes. Furthermore, limitations as well as tips and tricks are detailed in addition to management of common complications. Kidney Surgery for Urologists will be a valuable resource for Urologists, Urological Surgeons, Fellows in Urologic Oncology and Minimally Invasive/Robotic Surgery as well as upper level residents training in Urology.